Technostalgia, Nationalism, and the Extended Mind in Krapp's Last Tape. Issue 1 (April 2021) - Alba, Ken
Abstract : This article considers how Krapp's relationships with the various cognitive apparatuses he surrounds himself with prefigures what subjectivity looks like in the information age. The subjectivity that arises out of the complex interactions between the listener and their prosthetic memory can be characterised as what Olga Beloborodova has called 'postcognitivist'. Considering Krapp's relationship with his tapes from this postcognitivist perspective suggests how the construction of an abiding subject in the information age simultaneously depends upon and is imperilled by the particular technologies that project the voice into the dark. With that in mind, this article also explores how some users on the contemporary counterparts to Krapp's tapes – online platforms like YouTube, Reddit, and 4chan – weaponise the mediated nostalgia that infects Krapp's relationship with his own past to construct a nationalist political identity built on the manufacture of collective counterfactual memory.